On the use of recycled polyethylene terephthalate fiber in one-part geopolymer stabilized soft soil: Tensile performance and sustainability analysis - Zihan Zhou; Shuo Li; Guo Hu; Jun Wu; Chuanqin Yao; Fujun Niu (Developments in the Built Environment)
Aiming to promote low-carbon transformation of construction materials and waste upcycling solutions, this study adopted one-part geopolymer (OPG) as a sustainable binder for stabilizing soft soil. The recycled polyethylene terephthalate (RPET) fiber was also incorporated to enhance the stabilized soil's tensile strength. The effects of fly ash (FA) content, RPET fiber content and length on the tensile performance of the stabilized soil were investigated to reveal the synergistic mechanism between FA and RPET fiber. Results showed that the FA enhanced fiber-matrix deformation compatibility and improved fiber dispersion through its lubrication effects, significantly boosting the contribution of RPET fibers to the improvement of tensile strength of the stabilized soil. Life cycle assessment indicated that OPG-stabilized soil reduced carbon emissions, energy consumption, and costs by 78%, 58%, and 50% compared to ordinary Portland cement (OPC)-stabilized soil. The findings support OPG and RPET fiber's practical application in eco-friendly ground improvement and waste management.